2004
DOI: 10.1002/bem.20021
|View full text |Cite
|
Sign up to set email alerts
|

The dielectric properties of cancerous tissues in a nude mouse xenograft model

Abstract: The dielectric properties of various cancers, namely brain tumor, breast cancer, gastric carcinoma, and colon cancer, were measured in the frequency range of 500 MHz to 5 GHz. Cancers were cultivated applying the xenograft model of growing human cancerous tissues using the specific pathogen free, homo inbred mouse (a nude mouse). The complex permittivity was measured using an open-ended coaxial probe (HP85070B) and a computer controlled network analyzer (HP8510C). For the measurement of the dielectric properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 30 publications
3
44
1
Order By: Relevance
“…The conductivity of this tumor phantom is in the range of values for tumor cells obtained by Liu et al and Smith et al [14,15]; the permittivity is over those presented by Yoo et al [16] for less than 10%. In the speed of sound case there is a difference less than 3% regarding the values reported by Vlad et al [20], they found attenuation values between 0.34 dB/(MHz cm) and 0.91 dB/(MHz cm) which represent a maximum difference of 0.94 dB/(MHz cm); this value can be modified adding agarose or graphite in the mixture of the tumor phantom however it can affect the other values.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The conductivity of this tumor phantom is in the range of values for tumor cells obtained by Liu et al and Smith et al [14,15]; the permittivity is over those presented by Yoo et al [16] for less than 10%. In the speed of sound case there is a difference less than 3% regarding the values reported by Vlad et al [20], they found attenuation values between 0.34 dB/(MHz cm) and 0.91 dB/(MHz cm) which represent a maximum difference of 0.94 dB/(MHz cm); this value can be modified adding agarose or graphite in the mixture of the tumor phantom however it can affect the other values.…”
Section: Discussionmentioning
confidence: 82%
“…0´ (1) σ ε ε ω = where σ is the electrical conductivity, ε'' is the loss factor, ε 0 is the permittivity of free space and ω= 2πf is the angular frequency. According to [14,15] the conductivity of tumor cells and colon tumor is between 0.15 S/m and 0.5 S/m in the radio frequency range; and the permittivity constant value is near 70 at 200 MHz [16] for mice brain cancer, breast cancer, colon cancer and gastric carcinoma.…”
Section: Dielectric Properties Measurementmentioning
confidence: 99%
“…As mentioned in this paper, tumour size refers to the size of its diameter. Reconstruction of the brain image is based on the dielectric properties at 1 GHz and 2 GHz; therefore, the relative permittivity and conductivity for nominal Debye parameters evaluated at a frequency of 1.5 GHz are as in Table 1 [30][31][32]. The permittivity and conductivity values are reduced by 30% of its originally obtained values from the Debye formula except for the tumour as described in Table 2.…”
Section: Head Model Mri 2d Derived Modelmentioning
confidence: 99%
“…Such spheres simulated a cancerous tissue, a carcinoma in this case. Permittivity of carcinomas at 224 MHz is 59, and its electrical conductivity 0.9 [25,26]. Two sizes of spheres were used: 2.5 mL and 5.0 mL.…”
Section: Tumor and Ferrofluid Concentrationmentioning
confidence: 99%
“…5), their relative permittivity and electrical conductivity have to be similar to that of the tissues the phantoms mimic. Table 1 shows the values for the dielectric properties of muscle and carcinomous tissues (obtained from the literature) [23,26] as well as the experimentally measured values in our phantoms. As can be seen, dielectric properties achieved in the muscle phantom showed similar values to those reported in the literature; the differences in the relative permittivity and conductivity observed between phantoms and carcinomas were 3.8 units and 0.375 S/m, respectively.…”
Section: Agarose Muscle and Cancer Tumor Phantoms With Various Concenmentioning
confidence: 99%